The corewood of 25-year-old Hevea brasiliensis from two rubber plantations has high starch content - Cherelli, Sabrina Galetti; Bellasio, Chandra; Marcati, Carmen Regina [UNESP]; Rodrigues dos Santos, Thaís Paes [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Leonel, Magali [UNESP]; Ballarin, Adriano Wagner [UNESP] (Springer Nature, 2023)
In Brazil after 25 to 30 years of rubber production, when yield starts to drop, rubber trees are felled and destined for firewood and charcoal, despite the good mechanical properties and workability of the wood, and relatively low production costs. Wood with low starch content could be destined for the production of higher added-value products with potential to spare deforestation of many native forest species, but in rubberwood, starch increases palatability by wood borers and accelerates fungal degradation, thus compromising wood durability and the quality of timber. The aim of this study is to determine whether removal of the outer part of wood or varying the season of logging would result in wood with lower starch content. We measured the content of starch using enzymatic hydrolysis, the radial distribution of starch grains by light microscopy, and the corresponding seasonal variation of starch in 25-year-old felled trees. Rubberwood had large amount of starch in its entire trunk, increasing from the inner to the outer region, before decreasing in the outermost sapwood. Starch content was lower in summer, although higher than in other timber species. After relating the data to a comprehensive bibliographic survey of starch quantification in rubberwood, it was concluded that there are no technological arguments to destine the inner part of rubber tree trunks to the production of higher value products.